Association between preterm birth and its subtypes and maternal sociodemographic characteristics during the post-transitional phase in a developing country with a very high human development index. (June 2017) - Araya, B.M.; Díaz, M.; Paredes, D.; Ortiz, J.
Abstract: Objectives: Chile is a post-transitional country evolving towards a stationary population pyramid, which may be associated with increasing preterm birth (PTB) rates. This study aimed to compare maternal sociodemographic characteristics between the start of the post-transition phase (1994) and an established stage (2013) and to evaluate associations between these characteristics and PTB. Study design: An observational analytic design was conducted using national birth records ( n  = 4, 956, 311). Methods: Variables analysed in the 20 birth cohorts from 1994 to 2013 were: length of gestation (preterm <37 weeks) subdivided by gestational age (extreme, moderate/severe and late); maternal age (≤19, 20–35 and >35 years); education level (<8, 8–12 and >12 years of education); employment; marital status; area of residence; and type of birth (singleton, twins, and triplets or higher order). The prevalence of PTB was expressed as a percentage, and associations between PTB and predictor variables were analysed using logistic regression models. Results: Education level, age >35 years, maternal employment, unmarried status, twin delivery and urban residency rates increased between 1994 and 2013. According to the adjusted models, age >35 years and delivery of more than two foetuses were risk factors for all PTB subtypes. Maternal employment was a risk factor for moderate/severe, late and total PTB, and a low level of education was a risk factor for late and total PTB. On the other hand, age ≤19 years was protective against all PTB subtypes. Conclusions: All maternal characteristics changed between 1994 and 2013. Furthermore, the prevalence of PTB increased for all predictor variables studied over this period. Highlights: Comparison of maternal sociodemographic characteristics between the start of the post-transition phase (1994) and at an established stage (2013). The risk factors associated with all preterm births and subtypes were: maternal age over 35 years and deliveries of two or more foetuses. Being employed was a risk factor for moderate/severe, late and total preterm birth; low education level was a risk factor for late and total preterm birth. It is necessary to investigate the preterm birth risk factors identified in this study.